Principles of organization and structure of the management system of a holding type company - A. Borovikov; O. Smolyakov (Управление)
One of the main tasks of building an effective management structure for a group of companies of the holding type has been designated− it is the harmonization of the interests of top management and owners. The experience of improving the management systems of a number of really active groups of companies and diversified enterprises (including the sector of aviation and rocket engine building) focused on both scientific and technical, and production and commercial business, has been taken into account. Options for organizational structures of the group of companies have been considered. Attention has been drawn to the fact, that the choice of a variant of the structure of a group of companies should be the result of the agreements, reached between the decision-making center, investors and the top management of the management company.The basic functions of the basic elements of the structural bush of a group of companies have been formulated. In the multi-project management paradigm, the methodology of structure synthesis and the development of basic procedures for the management system of a holding-type group of companies have been considered, and the basic canonical structure of the management company and the project management apparatus of the production-scientific-commercial group of companies has been proposed, which includes two the main management units: the earning wing and the serving (control and analytical) wing. The features of the functioning of such key management units of the executive office and commercial management as analytical group, plan development and control group and market measurement group, have been considered.The importance of the vocational guidance component of the Directorate of Personnel Management, based on psychodiagnostic methods, has been noted. The basic functions of the management departments of the management company have been formulated, and the procedures for interaction between them have been enumerated in detail. The requirements for key management company personnel have been noticed. The option of material incentives for employees at the stage of promotion of the business unit has been proposed. It has been especially noted, that when making a decision on the improvement of existing management systems in enterprises, both technical and historical features of the realities in these corporations (enterprises) should be carefully considered.